Britorchestia, a new talitrid genus from western Europe and the Mediterranean Sea and a revision of Pseudorchestoidea and Sardorchestia (Crustacea, Amphipoda, Talitridae) - Lowry, J. K.; Bopiah, Arundathi (Zootaxa, 2012)
A new talitrid amphipod genus, Britorchestia from western Europe and the Mediterranean Sea is described here and the genera Pseudorchestoidea and Sardorchestia are redescribed.